Abroad Migration of Labor and Flow of Remittance in Nepal - Nepal, Pramshu (Kaladarpan कलादर्पण, 2024)
This paper defines and examines Nepal’s labor migration situation and remittance flow. In a similar manner, this study seeks to identify the main labor migration-related issues and suggests solutions. People in Nepal do not have access to employment prospects because of the country’s delayed industrialization. The socioeconomic standing of many migrant families has improved significantly as a result of labor migration. Although foreign employment improves the nation’s economic situation, it has also brought forth a great deal of issues. These issues should be addressed by the relevant sector, as failure to do so could have serious negative effects on our economy.